The life cycle of a butterfly - Linton, Margaret; Terry, Trevor (England : Wayland, 1988)
An illustrated study of the swallowtail butterfly, tracing each stage of its life cycle from conception to adulthood, with large type and pictures for the young and more detailed smaller type for older children.
Includes index.
Keywords: Butterflies -- Metamorphosis -- Juvenile literature; Butterflies -- Development -- Juvenile literature; Papilionidae -- Juvenile literature